Overview of the History of the Bukhara Branch of the Republic of Judicial Medical Expertise Scientific and Practical Center (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article provides information on the brief history of the Bukhara branch of the Republican Center for Forensic Medical Expertise.